Hierarchically hollow N-doped carbon-cobalt nanoparticle heterointerface for efficient bifunctional oxygen electrocatalysis. Issue 40 (23rd September 2022) - Leng, Xinyan; Ling, Cong; Lu, Xiao-Jie; Qin, Chenchen; Zhang, Jian; Li, Jing-Han; Xu, An-Wu; Yang, Zhengkun
Abstract : A novel organic-acid-assisted cleaving strategy fabricates hierarchically porous carbon nanocages with embedded Co nanoparticles for simultaneous ORR and OER. Abstract : The rational design and fabrication of high-performance and durable bifunctional non-noble-metal electrocatalysts for both the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are still a great challenge in the practical applications of rechargeable zinc–air (Zn–air) batteries. Herein, we report a simple yet robust route to synthesize cobalt nanoparticles rooted in the hierarchically hollow nitrogen-doped carbon frameworks (Co@HNCs). This strategy employs the pyrolysis of nanostructured hollow Co-based metal–organic framework (ZIF-67) precursors produced by selective linker cleaving with pyrazino(2, 3- f )(1, 10)phenanthroline-2, 3-dicarboxylic acid molecules (H2 PPDA). The designed hierarchically architecture is favorable for the accessibility of the active sites in the catalyst, which affords enhanced bifunctional performance for ORR and OER. Moreover, when used as a cathode in liquid and all-solid-state Zn–air batteries, the resultant Co@HNCs delivers high efficiency and outstanding durability, even outperforming the benchmark Pt/C + RuO2 . This work provides a feasible design avenue to achieve advanced dual-phasic oxygen electrocatalyst and promotes the development of rechargeable Zn–air batteries.